Digital Marketing’s Impact To Hospital Visits During Covid-19: A Systematic Review - Syafarudin A; Ayuningtyas D; Sari E (Syntax Corporation, 2022)
Background: The development of the digital era is very helpful to find solutions during the COVID-19 pandemic. This is not only beneficial for patients but also provides a place for digital marketing to see opportunities to restore public trust in health institutions, especially hospitals. Method: We searched the journals through the Pro Quest, Scopus, Springer link, Science Direct and Google Scholar database. We specify the inclusion and exclusion criteria. The Preferred Reporting Items for Systematic Reviews & Meta-Analyzes (PRISMA) 2009 instrument was used and a flowchart was prepared. Results: 1) Covid-19 had short term and long term effect for health industry including hospital, 2) digital technology helps health service providers including hospitals in engagement, innovation, and improvement for public service, 3) sosial media can be used to develop digital stategies including marketing in achieving specific goals, 4) poland’s hospital websites are of satisfactory quality and significanty optimize digital search, 5) the role of digital technology and digital marketing helps the difficulties of vorious health fields, 6) the COVID-19 pandemic is associated with reduce in on-site health services and an increase in digital facilities such as promotion and telemedice 7) in the era of digital health services, it can provide an evaluation of digital marketing with the aim of attracting costomers interest in choosing hospital service. Discussion: Digital marketing can affect the public's good view of health service providers and increase public trust in hospitals. Conclusion: 6 journals reviewed and Joanna Briggs Institute (JBI) and Critical Appraisal Skills Programme (CASP) were use to do critical appraisal. We conclude that social media affects the hospital visitations during COVID-19 pandemic